Immunostimulatory DNA inhibits IL-4–dependent IgE synthesis by human B cells - Horner, Anthony A.; Widhopf, George F.; Burger, Jan A.; Takabayashi, Kenji; Cinman, Nadya; Ronaghy, Arash; Spiegelberg, Hans L.; Raz, Eyal (Journal of allergy and clinical immunology, 2001)
Background: Immunostimulatory sequence oligodeoxynucleotide (ISS-ODN) is a potent antiallergic immunomodulating agent in mice. However, few studies have addressed its antiallergic potential in human subjects. Objective: We sought to determine whether a phosphoro-thioate ISS-ODN could inhibit IL-4–dependent IgE synthesis by human B cells. Methods: Initially, nonatopic- and atopic-donor PBMCs were incubated with ISS-ODN or mutated oligodeoxynucleotide, and cytokine production and B-cell expression of IFN-γ receptor and IL-4 receptor were measured by using ELISA and flow cytometry, respectively. In subsequent studies atopic-donor PBMCs were incubated with IL-4 alone or with ISS-ODN or mutated oligodeoxynucleotide. After 14 days, IgE production and IgM, IgG, and IgA production were determined by using ELISA. In select IgE studies cytokines were neutralized with mAbs. Results: ISS-ODN induced IL-12, IFN-α, IFN-γ, IL-10, and IL-6 production from both nonatopic- and atopic-donor PBMCs. ISS-ODN also increased IFN-γ receptor and inhibited IL-4 receptor expression on B cells from both donor populations. Furthermore, ISS-ODN inhibited IL-4–dependent IgE production by atopic-donor PBMCs. Neutralization of IL-12, IFN-α, IFN-γ, and IL-10, but not IL-6, attenuated the inhibitory activity of ISS-ODN on IgE production. In contrast to its inhibition of IgE synthesis, ISS-ODN stimulated the production of IgM, IgG, and IgA. Conclusion: These in vitro studies demonstrate that phos-phorothioate ISS-ODN elicits an innate immune response by PBMCs, which inhibits IL-4–dependent IgE synthesis. In addition, these results provide further support for consideration of ISS-ODN therapy for the treatment of allergic disease in clinical practice. (J Allergy Clin Immunol 2001;108:417-23.)